Surface modulated Fe doping of β‐Ni(OH)2 nanosheets for highly promoted oxygen evolution electrocatalysis - Shuisheng Hu; Yong Li; Daekyu Kim; Mengjie Liu; Lawrence Yoon Suk Lee; Kwok‐Yin Wong (EcoMat, 2022)
Abstract Active yet low‐cost electrocatalysts for water oxidation are crucial for the development of hydrogen energy economy. The Fe doping into Ni(OH)2 dramatically enhances catalytic activity toward oxygen evolution reaction (OER) but fabricating Ni(OH)2 of high Fe loading is still challenging. Herein, we report a one‐pot strategy to prepare disordered β‐Ni(OH)2 nanosheets with a high Fe doping level (9.9 at%, D‐Fe‐Ni(OH)2). By engaging 1,4‐phenylenediphosphonic acid (BDPA), FexBDPAy precursors are in situ generated in a growth solution containing Fe3+ ions, which decrease the reaction kinetics of Ni2+ and Fe3+ ions at the surface of Ni foam. This prevents the deconstructive hydrolysis by Fe3+ ions and enables a high Fe‐doping in D‐Fe‐Ni(OH)2. The as‐prepared D‐Fe‐Ni(OH)2 affords 10 mA cm−2 at an ultralow OER overpotential of 194 mV in alkaline media. This work offers a promising strategy of engaging organic ligands to achieve high‐doping levels for the construction of efficient electrocatalysts.